Dynamic analysis of serum Ca-125 levels during neoadjuvant chemotherapy in patients with advanced epithelial ovarian cancer: a retrospective study - Dharmarajan, Adarsh; Remya, A.; Krishnan, Aswathi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Assessment of CA-125 kinetics was commonly used as a tool for tumor response to chemotherapy in ovarian cancer patients. The study aimed to determine any logarithmic/linear relationship between pre-chemotherapy and pre-operative CA-125 levels in ovarian cancer. Methods: Total 52 patients who underwent neoadjuvant chemotherapy (NACT) followed by interval cytoreductive surgery were included. CA-125 levels before starting chemotherapy, during chemotherapy and the preoperative value, with the date of measurement recorded. Cox’s proportional hazards regression was used to evaluate univariate and independent multivariable association with the effect of clinical, pathological and CA-125 kinetic parameters on outcome endpoints. Results: The study couldn’t establish any relationship in logarithmic fall of CA-125 values among ovarian cancers as a result of neo-adjuvant chemotherapy. The disease-free survival among the patients was 12.2 months. Conclusions: There is an inverse relationship between serum CA-125 levels and survival in ovarian cancer. NACT resulted in adequate fall of CA-125 levels in most of the patients, but the rate of fall was not predictive of prognosis.